Calamus kebariensis (Arecaceae)—a new montane rattan from New Guinea - Maturbongs, Rudi A.; Dransfield, John; Baker, William (Phytotaxa, 2014)
Calamus kebariensis (Arecaceae or Palmae), a new species of rattan from the Bird’s Head Peninsula in West Papua, Indonesia, is described and illustrated. This species, which, among the New Guinea Calamus species, most closely resembles C. cuthbertsonii and C. spanostachys, is distinguished by its short and extremely slender stems, finely pinnate leaves and short, erect inflorescences that are branched to one order only in pistillate specimens.